“THE CHINGANA WAS FAMOUS ...”. POPULAR ENTERTAINMENT AND NATIONAL CULTURE IN SANTIAGO DE CHILE, 1820 -1840. - Donoso Fritz, Karen (Revista de Historia Social y de las Mentalidades, 2025)
The “chinganas” were suburban sites of  popular amusement strongly criticized by  liberal and conservative elites, on account of  the “immorality” practiced by their patrons.  However, the “chinganero” atmosphere  managed to penetrate the city center,  invading theaters and coffee-houses with its  characteristic dance, the “zamacueca”. The  inf luence of these cultural forms was such that  they became part of the national culture and  the official celebrations, as the elite proved  incapable of supplying its own cultural bases  for its nation-building discourse. This national  discourse was created by the elite to support  and propagate its national project, but it was the  popular traditions that gave it real content.
Keywords: People; Nation; “Chingana”; Culture